2005
DOI: 10.1007/s00417-005-1160-7
|View full text |Cite
|
Sign up to set email alerts
|

Topical brimonidine reduces collateral damage caused by laser photocoagulation for choroidal neovascularization

Abstract: Topical brimonidine improves the visual outcome of laser-treated classic extrafoveal or juxtafoveal CNV, possibly by protecting the neuroretina against collateral damage caused by the laser treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
0
10
0
2
Order By: Relevance
“…Furthermore, the ability of BMD to improve visual function is documented in rodent models of retinal disease. 35, 36, 37 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability of BMD to improve visual function is documented in rodent models of retinal disease. 35, 36, 37 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that topical brimonidine improved the visual outcome of patients undergoing laser treatment for classic extrafoveal or juxtafoveal choroidal neovascularization treatment [93] and that brimonidine, but not timolol, topical therapy, improved contrast sensitivity of glaucoma patients after 3 months of treatment [94].…”
Section: Brimonidinementioning
confidence: 99%
“…Этот эффект не связан с гипотензивной активностью бримонидина. Авторы полагают, что им можно объяснить сохранение зрительных функций у лабораторных живот ных в экспериментальных моделях глаукомы [32][33][34].…”
Section: бримонидин как нейропротекторный препаратunclassified